HEPATOPROTECTIVE AND ANTIDIABETIC EFFECT OF AQUEOUS EXTRACT OF CYNODON DACTYLON IN STREPTOZOTOCIN INDUCED DIABETIC RATS – HISTOLOGICAL STUDY - MADHANKUMAR S J; CHRISTILDA FELICIA JEBAKANI; SUNDARAPANDIAN (International Journal of Pharma and Bio Sciences, 2015)
Hepatoprotective Effect of aqueous extract of Cynodon dactylon (ACD) in streptozotocin (STZ) 45mg/kg body weight induced diabetic rats was studied. Oral administration of aqueous extract of Cynodon dactylon (ACD) to diabetic induced rats at a dose of 500 mg/kg body weight resulted in significant reduction of elevated blood glucose and hepatic transaminase enzyme levels, at different treatment period (0th day, 21st day, and45th day) which also showed the structural changes in hepatic architecture of STZ induced diabetic rats. The ACD treated diabetic rats were significantly recovered from hepatotoxicity,by analyzing various physical, biochemical parameters like body weight, fasting plasma glucose levels, Serum glutamate oxaloacetate transaminase(SGOT), Serum glutamate pyruvate transaminase (SGPT) and Alkaline phosphatase (ALP) levels. Further the histopathology results of ACD treated rats also confirmed the significant recovery of liver damage. Our study confirmed the therapeutic hepatoprotective effect of ACD in diabetic treated rats.